Corporate Governance and Financial Crises: Lessons from Singapore's Public Sector - Sam, Choon Yin (Prabandhan: Indian Journal of Management, 2011)
The Asian financial crisis, corporate scandals in the 2000s and the 2007 global financial crisis have one thing in common - corporate managers failed in their fiduciary duties to shareholders. Corporate managers were motivated by self interest and outright greed than the desire to maximize the long term interest of the corporations and shareholders. This paper argues for greater appreciation of the public sector style of governance. Because the private and public sector corporations are confronted with very similar problems, this paper attempts to draw some useful lessons from public sector governance by means of a case study. Although some of the lessons, such as paying competitive salaries, are not exclusively practiced nor originated in the public sector, it is useful to observe progress and innovations that the public sector has made over the years, and assess their implications to the private sector.